2016
DOI: 10.5847/wjem.j.1920-8642.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Critical care nurses' attitude towards life-sustaining treatments in South East Iran

Abstract: BACKGROUND: Life-sustaining treatments (LSTs) may prolong life but greatly decrease the quality of death. One factor influencing decision-making about withholding and withdrawing these treatments is the attitude of nurses. This study aimed to evaluate the attitude of critical care nurses towards life-sustaining treatments in South East Iran. METHODS:In this cross-sectional study, "Ethnicity and Attitudes towards Advance Care Directives Questionnaire" was used to investigate the attitude of 104 critical care nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…This study concludes that training Muslim nurses in respect of religious aspects of LST may improve their attitude. 12 The results of above study were not consistent with our study, as in our study, the experience of participation in resuscitation with a DNR order and the sex of participants did not have any effects on their attitudes. In another study in Iran, which Mogadasian et al conducted for the investigation of attitudes of Iranian nurses towards the DNR order at Tabriz University of Medical Sciences and Kurdistan University of Medical Sciences, the general attitude of nurses towards DNR was reported negative.…”
Section: Thiscontrasting
confidence: 84%
“…This study concludes that training Muslim nurses in respect of religious aspects of LST may improve their attitude. 12 The results of above study were not consistent with our study, as in our study, the experience of participation in resuscitation with a DNR order and the sex of participants did not have any effects on their attitudes. In another study in Iran, which Mogadasian et al conducted for the investigation of attitudes of Iranian nurses towards the DNR order at Tabriz University of Medical Sciences and Kurdistan University of Medical Sciences, the general attitude of nurses towards DNR was reported negative.…”
Section: Thiscontrasting
confidence: 84%
“…However, most studies in Iran opposed to withholding and withdrawing of life sustaining treatment. 28,29 Based on the above evidence, there is a general agreement on nonperforming active euthanasia in Muslim countries, including Iran. 19 Therefore, it is necessary to consider nurses' awareness of euthanasia and their reasons for agreeing or opposing with it using qualitative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in Turkey, the attitude of nurses in CCUs was more positive than nurses in other units and they were more knowledgeable about euthanasia. 16 Nurses in intensive care units seem to be more familiar with the concept of death and decision making about it 16,29 ; therefore, they probably have a more positive attitude toward euthanasia than nurses in general units and nursing students. But in this study, students had a more positive attitude toward euthanasia.…”
Section: Discussionmentioning
confidence: 99%
“…However, in other studies [9,12] gender was not a significant factor that affected attitude toward withdrawing life sustaining treatment. A study conducted in Iran showed that men were more positive attitude toward life -support and this result can be interpreted by male-dominant cultures [18].…”
Section: Characteristics Affecting Attitude Toward Life Sustaining Treatmentmentioning
confidence: 96%